PENGARUH KAPASITAS AEROB TERHADAP HASIL LATIHAN INTERVAL ANAEROB - Widodo, Slamet (Pendidikan Dan Kepelatihan Olahraga, 2008)
The aim of this research is to know (1) Influence of difference of aerob capacity to interval anaerobic training in improving speed runs 100 metre. (2) Group owning the make-up of achievement runs quickly 100 better metres between aerob capacity of high group and aerob capacity of low group. Method used at this research experiment method. At this research is compared to two experiment groups that is group 1 with capacities classification of aerobic high and group 2 with capacities classification of aerobic low. Both groups given are same treatment that is interval anaerobic training. Intake of achievement data run quickly 100 metre by doing tes run by pass through over 100 metre. Technique analyse data done with statistical analysis, using test of t at level of significant 5%. Result of research of Group 1 and group 2 owning difference which is significant, with value of tcount = 2,190 bigger than ttables 5% = 2.021. Group 1 owning the make-up of speed run 100 metre equal to 10.200%, while group 2 owning the make-up of speed run 100 metre equal to 8.283%. Capacities of aerob influence ability of runner to finish and overcome given practice burden. Capacities of Aerob not bad give base to appearance of speed. Capacities of Aerob represent the condition of common physical which is prerequisite for encumbering up at specialization. Conclusion: (1) There is difference of influence which is significant between aerob capacity of high group and aerob capacity of low group to make-up of achievement run quickly 100 metre. (2) Group aerob capacity of high have the make-up of achievement run quickly 100 better metres from at interval anaerobic training with aerob capacity of low.